Bi- und multilaterale Strategien der EU-Handelspolitik und ihre Auswirkungen auf entwicklungspolitische Zielsetzungen - Clemens Six; Karin Küblböck; Verena Katscher (Austrian Foundation for Development Research (ÖFSE), 2006)
Das vorliegende Papier bietet einen Überblick über die Handelsstrategien der EU und ihre Auswirkungen auf entwicklungspolitische Zielsetzungen. Der einleitende Teil enthält grundsätzliche Anmerkungen über Zusammenhänge zwischen Handel, Wachstum und Entwicklung. Der zweite Teil erläutert die internen Entscheidungsprozesse der EU in Handelsfragen. Dabei wird einerseits der fragmentierte Charakter der Kompetenzen und Entscheidungsmechanismen sowie andererseits das Demokratie- und Transparenzdefizit veranschaulicht. Anhand dreier konkreter Beispiele - dem Verhalten der EU in der WTO, der Gestaltung der Wirtschaftsbeziehungen zu den AKP-Staaten und dem bilateralen Freihandelsabkommen zwischen der EU und Südafrika - werden schließlich die politischen und wirtschaftlichen Konsequenzen der EU-Strategien erörtert. ... – – The European Union is the most important trading partner for developing countries in general and the Least Developed Countries in particular. Therefore, the internal strategic decisions of the European Union on trade policy have a large impact on the economic development of the south. This paper analyses the EU-trade policy in relation to development goals, starting with general remarks on the developmental potential of trade as such. In a next step, the internal decision making procedures of the Union are discussed helping to explain why the EU is currently unable to implement a coherent development policy, comprising various fields of policies. Finally, the paper selects three case studies, the EU as a major player in the multilateral trading regime of the WTO, the trading relations of the EU with the African-Caribbean- Pacific (ACP) countries and the bilateral free trade agreement between the EU and South-Africa (TDCA) to outline the conflicting interests and strategies applied by the Union in relation to developing countries. The results indicate that the relationship between trade and development is more complex than suggested by the assumptions of free-trade advocates.
Keywords: 330